An Evaluation on Developer’s Acceptance of EasySOC: A Development Model for Service-Oriented Computing - Mateos, Cristian M. (2010)
Due to the ever growing adoption of the Service-Oriented Computing (SOC) paradigm in the software industry, many researchers have been working on development models from the perspective of service requesters. The widely agreed development methodology involves three main activities, including service discovery, service incorporation into applications, and service replacement. This is because components within service-oriented applications need to invoke services that developers must discover, engage, and potentially replace with newer versions or even alternative services from different providers. EasySOC is a very recent approach for developing service-oriented applications that decreases the costs of building this kind of applications, by simplifying discovery, integration and replacement of services. This paper reports experiments evidencing the effort needed to start producing service– oriented applications with EasySOC. Results show that users non experienced in SOC development perceive that EasySOC is convenient and easy to adopt.